P057 Trends in recorded abortions in uk general practice – cohort study using clinical practice research datalink (CPRD). (8th June 2017) - Ma, Richard; Cecil, Elizabeth; Saxena, Sonia
Abstract : Introduction: Clinical Practice Research Datalink (CRPD) is a database of health records from participating general practices in the UK. Patients in the CPRD are broadly representative of UK population. We studied trends in recorded abortions between 2004 to 2014 in participating general practices in England and Wales. Methods: We created a cohort of females between ages of 15 to 44, registered with practices in England or Wales, during period 2004 to 2014. We identified abortions using Read codes. We removed records that were: misclassified, inaccurate in event and birth dates, and duplicates. We present trends in abortion data in women aged 15 to 44 in England and Wales using descriptive statistics and compared them with national data published by Department of Health (DH). Results: There were over 114, 000 recorded episodes of abortion between 2004 and 2014, with almost 5 million women of target age groups in the cohort. There appeared to be a consistent, year-on-year decrease in crude abortions rates from 2004 to 2014 using abortions data recorded on CPRD. The rate of decrease is less marked in the same period using national data. The age group 20–24 had the highest rate of abortions in every year, which correlates with national statistics. Discussion: There are similarities and differences in abortion data between CPRD and DH which might reflect differences in the way data are collected and recorded. We suggest abortion records on CPRD need further work on data validation before conducting robust epidemiological studies.